Importance of Modern Teaching Methods in English Language Teaching - Mukhammadieva Nargiza (Genius Publishing Group, 2022)
This article talks about the importance of modern teaching methods in English language teaching. The modern method of teaching English is built on the basis of the classical method of learning foreign languages. One of the important tasks and goals of modern methods is teaching communication and mastery of speech means. At the same time, each technique has distinctive features, due to a combination of different methods, techniques and means.
Keywords: Linguistics; methodology; speech; dictionary